The Role of Animated Videos on Students' Creative Thinking in Elementary School - Mariam, Devi; Harmawati, H; Sa'diah, Tia Latifatul (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This study aims to reveal the effect of animated video media on students' creative thinking in IPAS learning. This research uses pre-experimental design method with Pre-Experimental Design research type and static group comparison design. This design involves two classes, namely the experimental class and the control class. Therefore, two tests were conducted, namely pretest (O1) and posttest (O2). In the validation test, five questions met or exceeded the r-table number. The reliability test produced a figure of 0.916 which exceeded 0.70, proving that the results of this test were reliable. After the validity and reliability tests, testing was carried out again on five questions that met the r-table, which was carried out twice, namely the pretest and posttest. The pretest and posttest results were tested again with an average minimum value of 62.16, a median of 60.00, and an overall value of 6216. Normality test using One-Sample Kolmogorov-Smirnov Test showed results > 0.05. The homogeneity test shows the same number which is > 0.005. In the t test using the independent samples test, the group statistic shows an average pretest of 55.84 and posttest of 68.48. Independent samples test obtained a significance value of 0.608, proving that the pretest and posttest are homogeneous. The difference between the two is -12.640, indicating that the pretest < posttest, so the animation media has an influence on students' creative thinking in elementary school..